Making extra room for carotenoids in plant cells: New opportunities for biofortification. (November 2021) - Torres-Montilla, Salvador; Rodriguez-Concepcion, Manuel
Abstract: Plant carotenoids are essential for photosynthesis and photoprotection and provide colors in the yellow to red range to non-photosynthetic organs such as petals and ripe fruits. They are also the precursors of biologically active molecules not only in plants (including hormones and retrograde signals) but also in animals (including retinoids such as vitamin A). A carotenoid-rich diet has been associated with improved health and cognitive capacity in humans, whereas the use of carotenoids as natural pigments is widespread in the agrofood and cosmetic industries. The nutritional and economic relevance of carotenoids has spurred a large number of biotechnological strategies to enrich plant tissues with carotenoids. Most of such approaches to alter carotenoid contents in plants have been focused on manipulating their biosynthesis or degradation, whereas improving carotenoid sink capacity in plant tissues has received much less attention. Our knowledge on the molecular mechanisms influencing carotenoid storage in plants has substantially grown in the last years, opening new opportunities for carotenoid biofortification. Here we will review these advances with a particular focus on those creating extra room for carotenoids in plant cells either by promoting the differentiation of carotenoid-sequestering structures within plastids or by transferring carotenoid production to the cytosol.